Exploring Psilocybe spp. mycelium and fruiting body chemistry for potential therapeutic compounds - Waldbillig, Adam; Baranova, Maria; Neumann, Sarah; Andrade, Jonathan; Sidhu, Sharan (Frontiers in Fungal Biology, 2023)
Psilocybe mushrooms, otherwise known as “magic” mushrooms, owe their psychedelic effect to psilocin, a serotonin subtype 2A (5-HT2A) receptor agonist and metabolite of psilocybin, the primary indole alkaloid found in Psilocybe species. Metabolomics is an advanced fingerprinting tool that can be utilized to identify the differences among fungal life stages that may otherwise be unaccounted for. In this study, by using targeted and untargeted (metabolomic) multivariate analysis, we demonstrate that the chemical composition of Psilocybe differs among mycelia, grain mycelia, and fruiting bodies. The preferential accumulation of psilocybin, baeocystin, tryptophan, ergothioneine, and phenylethylamine in fruiting bodies differentiated them from mycelia; however, the levels of alpha-glycerylphosphorylcholine (α-GPC), N-acetylglucosamine, and trimethylglycine were found to be proportionally higher in mycelia than in fruiting bodies based on Pareto-scaled data. Considering the wealth of compounds with therapeutic potential that have been isolated from various fungal genera, it would be pertinent to study the compounds found in Psilocybe mycelia as potential naturally derived therapeutic targets.